Our Brain - Thanopoulou, Maria; Felouka, Alexandra; Anterrioti, Maria (Open Schools Journal for Open Science, 2024)
This proposition consists of the project we took part in, regarding our brain. Through our presentation, we present the function of the brain briefly, as well as the importance of it. Moreover, the two different parts of the human brain are analyzed. Lastly, we also refer to the lead differences between the male and the female brain.